YeastRGB: comparing the abundance and localization of yeast proteins across cells and libraries - Dubreuil, Benjamin; Duan, Yuanqiang; Meurer, Matthias; Knop, Michael (Nucleic acids research, 2019)
Abstract. The ability to measure the abundance and visualize the localization of proteins across the yeast proteome has stimulated hypotheses on gene function